Caso de estudio : vías de cuarta generación en Colombia (2020)
This case study looks to learn first-hand the details of the financial and legal model for the awarding of fourth generation road concessions in Colombia in order to set an academic precedent for analysis of the issue. In this way, this research is intended the case study was based on a bibliographic review in which documents from newspapers, minutes, public documents, analysis of financial companies and reports from international and multilateral banks were used. Finally, the shortcomings and improvements that the road concessions in the country may have were highlighted, such as inaccuracies in the 4G model of road concessions, such as errors in the calculation of road flow, cadastral problems that prevented the progress of the works, lack of support from social investments and the technological backwardness of most public entities involved in this type of public-private partnerships, all these problems are analyzed in greater detail in this document.